PENGARUH PEMBERIAN TUNJANGAN KINERJA TERHADAP OPTIMALISASI KINERJA KARYAWAN FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN UNIVERSITAS NEGERI SURABAYA - GUSTI PUTRI CITTA SUCI, NI (Jurnal Akuntansi AKUNESA, 2015)
AbstractThis study was intended to identify the impact of the performance benefit on the optimalization the performance of employees in Faculty of Mathematical and science at state university of Surabaya. The population in this study were all employees of the Faculty of Mathematics and Natural Sciences who obtain performance benefits as many as 35 people. This study is included in a qualitative approach and data used in this study are primary data da secondary data. Methods of data collection using the method of observation and in-depth interviews. Further data analysis is done by comparing each of the answers received from respondents. The result of the study showed that performance of employees in faculty of Mathematical and science at state university of Surabaya is quite optimal after the performance benefit. Keyword: performance benefits, employee performance, optimalization, duties and function, reward